2018
DOI: 10.1038/s41413-018-0029-4
|View full text |Cite|
|
Sign up to set email alerts
|

Alpl prevents bone ageing sensitivity by specifically regulating senescence and differentiation in mesenchymal stem cells

Abstract: Mutations in the liver/bone/kidney alkaline phosphatase (Alpl) gene cause hypophosphatasia (HPP) and early-onset bone dysplasia, suggesting that this gene is a key factor in human bone development. However, how and where Alpl acts in bone ageing is largely unknown. Here, we determined that ablation of Alpl induces prototypical premature bone ageing characteristics, including bone mass loss and marrow fat gain coupled with elevated expression of p16INK4A (p16) and p53 due to senescence and impaired differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 54 publications
3
52
0
4
Order By: Relevance
“…Likewise, genes associated with intestinal, hair follicle and neural stem cells (NSCs), such hopx and alpl are strongly expressed in mantle, A/P, and amplifying cells adjacent to mantle cells, but are downregulated in central support cells, forming a ring of expression similarly to fndc7rs4 (Fig. 1O, 3G, (Li et al, 2015a;Liu et al, 2018). Genes specifically expressed in central support cells beneath the hair cells likewise express genes that label stem cells in other organs, such as fabp7/Blbp, which labels glioma stem cells, radial glia cells, NSCs, (Kim et al, 2016;Morihiro et al, 2013) and isl1 that is expressed in quiescent intestinal stem cells and stem cells in the heart (Makarev and Gorivodsky, 2014;Shin et al, 2015).…”
Section: Support Cells Share Gene Expression Profiles With Stem Cellsmentioning
confidence: 99%
“…Likewise, genes associated with intestinal, hair follicle and neural stem cells (NSCs), such hopx and alpl are strongly expressed in mantle, A/P, and amplifying cells adjacent to mantle cells, but are downregulated in central support cells, forming a ring of expression similarly to fndc7rs4 (Fig. 1O, 3G, (Li et al, 2015a;Liu et al, 2018). Genes specifically expressed in central support cells beneath the hair cells likewise express genes that label stem cells in other organs, such as fabp7/Blbp, which labels glioma stem cells, radial glia cells, NSCs, (Kim et al, 2016;Morihiro et al, 2013) and isl1 that is expressed in quiescent intestinal stem cells and stem cells in the heart (Makarev and Gorivodsky, 2014;Shin et al, 2015).…”
Section: Support Cells Share Gene Expression Profiles With Stem Cellsmentioning
confidence: 99%
“…With age, BMSCs are more inclined to undergo differentiation into adipocytes rather than osteoblast, resulting in an increased number of adipocytes and a decresed number of osteoblasts, causing osteoporosis . Our previous study also showed that ALPL governed the osteo-adipogenic balance of BMSCs and prevent cell senescence (Liu et al, 2018). Alkaline phosphatase is known as a ubiquitous plasma membrane-bound enzyme (ectoenzyme), which hydrolyzes several different molecules at physiological (neutral) and alkaline pH, including inorganic pyrophosphate (Russell, 1965), pyridoxal-5-phosphate (the active form of vitamin B6) (Whyte et al, 1985) and nucleotides (Ciancaglini et al, 2010;Scheibe et al, 2000;Zimmermann, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Adult HPP patients showed early loss of primary or secondary teeth, osteoporosis, bone pain, chondrocalcinosis, and fractures. Our previous study found age-related bone mass loss and marrow fat gain in heterozygous Alpl +/mice (Liu et al, 2018). Bone marrow mesenchymal stem cells (BMSCs) are multipotent cells capable of differentiating into various cell lineages including osteoblasts and adipoytes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found age-related bone mass loss and marrow fat gain in heterozygous Alpl +/− mice. 3 Bone marrow mesenchymal stem cells (BMSCs) are multipotent cells capable of differentiating into various cell lineages, including osteoblasts and adipocytes. As age increases, BMSCs are more inclined to undergo differentiation into adipocytes rather than osteoblasts, resulting in an increased number of adipocytes and a decreased number of osteoblasts, which leads to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Our previous study also showed that ALPL governed the osteo-adipogenic balance in BMSCs and prevented cell senescence. 3 ALPL is a ubiquitous plasma membrane-bound enzyme (ectoenzyme) that functions at physiological (neutral) and alkaline pH to hydrolyze several different molecules, including inorganic pyrophosphate, 5 pyridoxal-5-phosphate (the active form of vitamin B6), 6 and nucleotides. [7][8][9] However, the detailed mechanism of ALPL causing age-related osteoporosis is largely unknown.…”
Section: Introductionmentioning
confidence: 99%